Broń barbarzyńców w attyckim malarstwie wazowym VI-V w. p.n.e. Wybrane zagadnienia - Mielczarek, Mariusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Among representations оf Barbarians in Greek art, vase paintings performed in Attic workshops in the second half of the 6th and 5th century В.C. can be distinguished. In order to estimate the state of knowledge among the Greeks from Attica about weapons used by the Barbarians, comparative studies have been carried out on the representations of Black Sea Scythians and Ethiopians, that is individuals characterised by distinct negroidal features. In the Attic vase painting the representations of Scythians are more numerous than those of the Ethiopians. Among images of Scythian warriors appear horsemen and footwarriors. The repertoire of weapon in hands of the Scythians as presented by the Attic artists is very limited. Most often occurring weapon was a bow, which indicates a non Greek origin of the warriors. A characteristic Scythian axe is presented rarely. The fact that a bow and an axe are the only other types of weapon appearing in vase paintings does not necessarily imply lack of knowledge. There are reasons to assume that the weapon used by Scythians was well known to the Greeks. Representations o f the Scythians on the goods produced in the Bosporan workshops are the evidence. Attention should be also paid to the issue of the presence of Scythians in Athens. Referring to the Ethiopians, light-armed footwarriors were mainly presented. A bow and an axe were their basic offensive weapons, whereas pelta was a protective weapon. It is easily noticeable that the repertoire of armament of the Scythians' and the Ethiopians’ presented by Attic artists does not fully correspond to the reality. It was reduced to these types of weapon which were not typical for the Greeks at the times when the patterns of representation of a Barbarian warrior was created.